Reactions of tert-butyl N,N-diethyl-N '-(4-phenylthiazol-2-yl)phosphorodiamidite with electrophilic reagents - Sal’keeva, L. K.; Nurmaganbetova, M. T.; Minaeva, E. V.; Kokzhalova, B. Z. (Nauka/Interperiodica, 2006)
Previously unknown amidophosphorous acid derivatives were prepared by transamidation of tert-butyl N,N-diethyl-N'-(4-phenylthiazolyl)phosphorodiamidite with 2-amino-4-phenylthiazole, and their reactions with acetyl and benzoyl chloride were studied. These reactions are shown to proceed regioselectively according to the Arbuzov scheme to give the corresponding ketophosphonates. The reaction of the phosphorodiamidite with acetyl chloride in a I : 2 molar ratio involves formation of acetophosphonate that reacts in the enol form to give the corresponding (1-acetoxy)vinylphosphonate.